An issue of limits. In regards to Elvio Fassone's "Fine pena ora" (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The paper frames some of the most relevant questions developed in the book Fine pena: ora  written by Elvio Fassone (Sellerio, 2015) within the perspective of a new constitutional criminal law. In particular, it looks at the problem of the absolute type legislative presumptions, based on criminal law. To the need of tailoring the prison treatment would seem to have to correspond a more incisive role of the judge, that otherwise is deprived of its most important functions.